Note the effects of bagging on pod, bean, and chocolate quality of cacao (Theobroma cacao L.) - Rabia, A. P.; Protacio, C. M. (1996)
Bagged pods had significantly lower levels of damage due to insect pests and pathogens, had larger volume, contained relatively bigger beans with higher bean dry weight recovery per pod than the control. Sensory evaluation of tableya (round raw chocolate) made from beans of bagged pods revealed no significant difference in taste from the control
Keywords: Cacao; Cocoa processing; Crop productions